Warming modulates the photosynthetic performance of Thalassiosira pseudonana in response to UV radiation - Xu, Zhiguang; Yang, Shunda; Li, Mingze; Bao, Menglin; Wu, Hongyan (Frontiers in Microbiology, 2023)
Diatoms form a major component of phytoplankton. These eukaryotic organisms are responsible for approximately 40% of primary productivity in the oceans and contribute significantly to the food web. Here, the influences of ultraviolet radiation (UVR) and ocean warming on diatom photosynthesis were investigated in Thalassiosira pseudonana. The organism was grown at two temperatures, namely, 18 o C, the present surface water temperature in summer, and 24°C, an estimate of surface temperature in the year 2100, under conditions of high photosynthetically active radiation (P, 400-700 nm) alone or in combination with UVR (P+UVR, 295-700 nm).It was found that the maximum photochemical yield of PSII (Fv/Fm) in T. pseudonana was significantly decreased by the radiation exposure with UVR at low temperature, while the rise of temperature alleviated the inhibition induced by UVR. The analysis of PSII subunits turnover showed that high temperature alone or worked synergistically with UVR provoking fast removal of PsbA protein (KPsbA), and also could maintain high PsbD pool in T. pseudonana cells. With the facilitation of PSII repair process, less non-photochemical quenching (NPQ) occurred at high temperature when cells were exposed to P or P+UVR. In addition, irrespective of radiation treatments, high temperature stimulated the induction of SOD activity, which partly contributed to the higher PSII repair rate constant (Krec) as compared to KPsbA. Our findings suggest that the rise in temperature could benefit the photosynthetic performance of T. pseudonana via modulation of its PSII repair cycle and protective capacity, affecting its abundance in phytoplankton in the future warming ocean.